Airport 1975 - Smight, Jack.; Heston, Charlton; George Kennedy; Gloria Swanson; Karen Black (USA Universal Pictures, 1974)
A mid-air collision involving a a small plane and a commercial jetliner leads to potential disaster, as a plane loaded with passengers and no pilot becomes the worst nightmare for a flight attendant tasked with flying the craft.
A 747 in flight collides with a small plane, and is rendered pilotless. Somehow the control tower must get a pilot aboard so the jet can land.
Arthur Hailey
Language : English Subtitles : No Subtitle
Keywords: Action; Thriller; Drama